Studi Kasus Analisis Pendapatan Usaha Copasme di Kota Palangka Raya - Asro Laelani Indrayanti; Elyta Vivi Yanti; Arief Rahman Hakim (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Technological innovation in local food products is absolutely necessary, by creating the added value in such a way as local products so that the products produced have more or at least the same value as local products. The result of the creation of local products, Copasme able to meet the growing demands of global consumers, namely in addition to demanding aspects of pleasure, the enjoyment of local products, consumers still want aspects of health and safety. Copasme is one of the alternative drink sachets developed in Palangkaraya City. From the analysis of copasme sachet business during one period (per month) it is known that (1) production cost is IDR. 6,472,000.00 (2) revenue of IDR. 21,600,000.00, (3) Net income / profit of IDR. 15,128,000.00 (4) Efficiency of 3.3. This shows that the sachet copas business is efficient or feasible.